Fuat Sezgin's Thoughts on Hadith Criticism: Revisiting Ignaz Goldziher's Views on Doubts about the Authenticity of Hadith - Nasir, Muhammad Alwi; Zulfahmi Alwi; Siti Aisyah Kara (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Ignaz Goldziher's views on hadith have elicited both support and criticism from Muslim scholars. Fuat Sezgin, a prominent Islamic scholar, disputed Goldziher's claim that hadiths narrated by classical scholars were inauthentic due to their reliance on sanad rather than matan criticism. Sezgin contends that the oral tradition of hadith transmission and his identification of some false hadiths in Sahih Bukhari weaken Goldziher's argument. This paper examines the differing perspectives of Ignaz Goldziher and Fuat Sezgin on hadith. Utilizing a literature research approach, it employs a descriptive-analytical method to elucidate the ideas of these two scholars. The research concludes that Goldziher's critique arose from a fundamental misunderstanding, as the narration method he criticized differed from that of classical scholars. Furthermore, the assertion that hadith was not documented in writing until later stages is refuted, as the Companions had recorded it in the Shahifah during the Prophet's time. Goldziher's identification of false hadiths in Bukhari is attributed to his focus on matan, leading him to consider them as fabrications by Bukhari.